The Relationship of Sex and Parents' Education with Adolescent's Knowledge About the Prevention of Transmission of HIV/AIDS - Nina Sri; Dewi Susilawati; Febi Puji Utami (Healthy-Mu Journal, 2023)
Adolescence is a transition period from children to adults. At this time there were many changes, especially in physical development so that teenagers' curiosity about many things was high, especially in terms of sexuality. Teenagers' ignorance about the dangers of HIV/AIDS makes adolescents an age group at risk of contracting HIV/AIDS. Methods: this type of research is quantitative research, while the research design used is cross sectional. The population of the study was 286 and the number of samples was 74 students who were taken using the Probability Sampling technique with the sampling method using proportional stratified random sampling. Results: the results of statistical tests using the Chi-Square test showed that there was a relationship between gender (Pvalue=0.001, OR=10.182) and parental education (Pvalue=0.004, OR=4.852) with adolescent knowledge about preventing HIV/AIDS transmission. Conclusion: Health education needs to be done to increase adolescent knowledge about sexuality and prevention of HIV/AIDS transmission. The participation of parents, schools and health care facilities in providing reproductive health education, especially related to HIV/AIDS is very important.